Inés Amor y los primeros años de la Galería de Arte Mexicano, de Eréndira Derbez (REVISTA NODO, 2026)
Through exhaustive research in the archives of the Mexican Art Gallery, Eréndira Derbez takes us to discover how Inés Amor made her way in a male-dominated world and defied stereotypes to become one of the most influential figures in Mexican art.